Minimum standards for maximum pricing constraints - Mark A. Jamison (American Enterprise Institute (AEI), 2024)
Government regulators often establish maximum prices for regulated services. This paper explains the proper economic principles for establishing such constraints. The principles imply a range - an upper limit and a lower limit - that constrain the regulator's discretion. Principles emerging from common law and from economic research align, indicating that, at a minimum, suppliers should have the opportunity to recover the costs created by production and by regulations, as well as costs previously incurred that the regulation makes unrecoverable from the marketplace. Costs created by the regulation include forwardlooking production costs for the service in question and for other impacted services, and changes in revenue from other services. Stand-alone costs, incremental costs, and customer willingness to pay serve as bounds in the case where customer options are restricted to subsets of services provided by the firm in question. When customers can seek service from providers that supply services not offered by the regulated firm, and that exhibit economies of joint production, the upper bound on regulated prices is lower than stand-alone costs and the bound is higher than incremental costs. Cases discussed include railroads, utilities, broadband, and housing.
Keywords: K23; L51; L86; L92; 330; prices; cross-subsidy; regulation; competition